2018
DOI: 10.3390/ijms19102996
|View full text |Cite
|
Sign up to set email alerts
|

Human Mesenchymal Stem Cell Secretome from Bone Marrow or Adipose-Derived Tissue Sources for Treatment of Hypoxia-Induced Pulmonary Epithelial Injury

Abstract: Alveolar epithelial dysfunction induced by hypoxic stress plays a significant role in the pathological process of lung ischemia-reperfusion injury (IRI). Mesenchymal stem cell (MSC) therapies have demonstrated efficacy in exerting protective immunomodulatory effects, thereby reducing airway inflammation in several pulmonary diseases. Aim: This study assesses the protective effects of MSC secretome from different cell sources, human bone marrow (BMSC) and adipose tissue (ADSC), in attenuating hypoxia-induced ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 74 publications
(81 reference statements)
1
34
0
Order By: Relevance
“…MSCs expedite and promote recovery in animal models of ALI which include Escherichia coli endotoxin-induced, hypoxia-induced, LPS-induced and ventilator induced lung injury [134][135][136][137][138]. In a systematic review of 17 published preclinical animal model studies that reported on mortality, McIntyre et al were able to show that treatment with MSCs, as compared to controls, significantly decreased the overall odds of death in animals with acute lung injury [139].…”
Section: Preclinical Studies Of Msc Therapy In Acute Lung Injury (Ali)mentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs expedite and promote recovery in animal models of ALI which include Escherichia coli endotoxin-induced, hypoxia-induced, LPS-induced and ventilator induced lung injury [134][135][136][137][138]. In a systematic review of 17 published preclinical animal model studies that reported on mortality, McIntyre et al were able to show that treatment with MSCs, as compared to controls, significantly decreased the overall odds of death in animals with acute lung injury [139].…”
Section: Preclinical Studies Of Msc Therapy In Acute Lung Injury (Ali)mentioning
confidence: 99%
“…In a systematic review of 17 published preclinical animal model studies that reported on mortality, McIntyre et al were able to show that treatment with MSCs, as compared to controls, significantly decreased the overall odds of death in animals with acute lung injury [139]. In these models, the mechanism of the repair process is attributed to inhibiting TNF-α release, enhancing IL-10 secretion, decreasing IL-6 levels, increasing KGF, overexpression of angiopoietin-1, reprogramming of macrophage function and secretion of antimicrobial peptides [137,138].…”
Section: Preclinical Studies Of Msc Therapy In Acute Lung Injury (Ali)mentioning
confidence: 99%
“…However, data correlated to the molecular and cellular mechanisms underlying hypoxic and reperfusion lung damage are limited. Moreover, the majority of the studies are focused on endothelial and epithelial cells rather than alveolar macrophages that have critical immunological functions in acute lung injuries including ischemia reperfusion lung injury [10,17,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are the most widely used cell type for cell transplantation‐based treatments, because of their ability to differentiate into multiple lineages, as well as the ease in which they can be isolated from different tissue sources and propagated . MSCs derived from bone marrow, adipose tissue, muscles, and ESCs are currently being used to treat various diseases and conditions, such as myocardial ischemia, stroke, and musculoskeletal disease, with the idea being that the transplantation of MSCs near the sites of damaged tissue results in their differentiation and reconstitution of the tissue, such that it regains functionality. For example, percutaneous injection of bone marrow‐derived MSCs into the damaged myocardium in a pig model of myocardial ischemia reduced the extent of necrosis, promoted the regeneration of contractile myocardium, and improved overall cardiac function …”
Section: Introductionmentioning
confidence: 99%